Intense vortex pinning enhanced by semicrystalline defect traps in self-aligned nanostructured MgB2 - Li, S. (2011)
In this work, we report the discovery of a vortex pinning source: semicrystalline defect wells in self-aligned nanostructured MgB2. It is demonstrated that these aperiodic regions trap numerous crystal defects migrating along nanodomain boundaries during self-alignment and act as intense vortex pinning centers that significantly enhance the high-field performance of MgB2. This suggests that the density of trapped defects in the wells is much greater than that found in other vortex pinning sources.